METODE TAFFLER DAN ALTMAN Z-SCORE DALAM MENGUKUR FINANCIAL DISTRESS PADA PT TIRTA MAHAKAM RESOURCES, Tbk. - Sepbeariska Manurung; Liper Siregar; Eliza Arshandy; Daud Immanuel Hutagalung (Jurnal Ilmiah Satyagraha, 2025)
This study aims to predict the level of bankruptcy of a company using the Tafflerand Altman Z-Score methods at PT Tirta Mahakam Resources, Tbk. for the period 2015-2022and to determine the comparison of the accuracy and error rate of each method used, namelythe Taffler and Altman Z-Score methods. This study uses quantitative data by taking secondarydata accessed from the official website of the Indonesia Stock Exchange (www.idx.co.id). Thedata analysis technique used is descriptive qualitative and comparative analysis. The results ofthis study indicate that there are different results in predicting the level of bankruptcy producedusing the Taffler method in contrast to the Altman Z-Score method. This can be seen from thehighest level of accuracy is using the Altman Z-Score method with a percentage of 0% whilethe error rate is using the Altman Z-Score with a percentage of 100%. Thus it can be concludedthat the most suitable and accurate method in predicting Financial Distress is the Altman ZScoremethod.